Peranan Promosi Energi Drink terhadap Minat Beli Produk M-150 di Kota Tangerang - Sri Sukartono Natadiharja (Syntax Corporation Indonesia, 2024)
One of the existing energy drinks is an energy drink with a product of the brand M-150 that is currently owned by people, due to its good properties and constant promotion. Many factors that may influence the interest in purchasing M-150 energy drinks are the promotional roles offered, especially for the people of Tangerang City, Tangerang City and surrounding areas. The research population is 500 consumers in the Tangerang City area of Tangerang City who consume M-150, the author chose this area because it is a strategic location in the eastern part of Tangerang City bordering DKI Jakarta and many retailers offer its products, one of which is M-150, so there are many possibilities for consumers to buy these products. The study sample used 100 respondents. The sampling method in the study was carried out using a simple random sampling technique. The data type is primary. Data collection method using questionnaires. The analysis technique uses multiple regression. The results of the analysis using SPSS Version 19 showed that: 1) Public relations, advertising, sales promotion, direct marketing and personal selling indicators were well responded by respondents. Respondents in general also have a fairly high buying interest in M-150 energy drink products, both from cognitive, affective and coative aspects.